EVALUATION OF EXOTIC POTATO GERMPLASM FOR HIGH YIELD AND DISEASE RESISTANCE UNDER LOCAL CONDITIONS - A. Shehroz; M. M. Hussain; I. Ramzan; M. A. Ali (Journal of Animal and Plant Sciences, 2018)
Potato is an important food crop of Pakistan due to its high usage in food processing industry. This study was carried out at Potato Research Institute, Sahiwal. The plantation was done by maintaining plant to plant and row to row distances as 20 and 75 cm respectively. Potato varieties were screened against three diseases such as common scab, rhizoctonia, cracking and various tuber attributes such as germination, tuber size and yield were also evaluated. It was revealed from the data that potato variety 171 gave the highest yield of 35.5 t/ha followed by Masai with 31.0 t/ha. The maximum emergence was shown by the Variety Red Sun 89.7%. However, the lowest emergence was shown by the variety Camel 71.7%. Regarding tuber grades, it was noted that the maximum tuber size were produced by the Compass (3.7%), whereas 11 varieties did not produce large size tubers at all. The variety Red Sun produced lowest percentage of small size tubers 12.7%, whereas maximum small size tubers ( 93.0%) were produced by the variety Jitka. Regarding diseases data, it was noticed that the maximum scab incidence 4% was recorded on the variety Masai, maximum rhizoctonia attack 60% was recorded on the variety Camel and maximum tuber cracking (0.7%) was noted on the variety Vendulla. The results conclude that several exotic potato varieties identified during this study could be adapted for local cultivation to enhance potato production in the country. different countries brings diseases with them (Secor and
Keywords: Cracking; exotic germplasm; disease resistance; potato; tuber yield.